Differentiation of Self among Students at Higher Secondary School Level in Relation to Their Decision -Making Capacity - Gopinath, Geetha; N. S., Vijayalekshmi (International Journal of Psychosocial Rehabilitation, 2020)
The modern context requires people at all levels to take appropriate decisions in life situations. This can only occur in a person who is differentiated at the level of the self in a balanced manner. This process starts in the family at an early stage. This study evaluates the level of differentiation of self among 300 higher secondary school students (169 males, 131 females) in Kerala and their ability to make decisions. It also tries to find the correlation between differentiation of self and decision making. The findings indicate the need for greater level of differentiation of self and development of decision-making skills among students. This study also found that there is good correlation between differentiation of self and decision making.